MOBILE APPLICATION TO SUPPORT SAFER MEDICATION DECISION MAKING AND BEHAVIOR OF OLDER ADULTS. (11th November 2018) - Holden, R J; Srinivas, P; Campell, N L; Clark, D O; Bodke, K S; Boustani, M A; Ferguson, D; Callahan, C M
Abstract: The National Academy of Medicine and others promote interventional research to reduce older adults' use of over-the-counter (OTC) and prescription medications with anticholinergic effects. The Indiana University Brain Health Patient Safety Laboratory performed a study to develop and test a mobile software application to intervene on older adults' anticholinergic medication use. In the first study phase, we performed qualitative research interviews (n=24), in-store shopper observations (n=39), and laboratory-based simulated OTC shopping tasks (n=21). This phase produced a dual-process conceptual model of OTC medication purchase and use, separating habit-based and deliberation-based decision-making processes. Based on this model, we iteratively developed and usability tested Brain Buddy, a mobile app intended to: increase awareness through videos and articles; support decision making through decision aid and risk scoring features; and assist users to have a conversation with their prescriber or pharmacist. A pilot of Brain Buddy's effect on older outpatients' behavior is currently underway.